2012
DOI: 10.1128/aem.07191-11
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Symbiotic Organs and Bacterial Endosymbionts of Lygaeoid Bugs of the Families Blissidae and Lygaeidae (Hemiptera: Heteroptera: Lygaeoidea)

Abstract: Here we present comparative data on the localization and identity of intracellular symbionts among the superfamily Lygaeoidea (Insecta: Hemiptera: Heteroptera: Pentatomomorpha). Five different lygaeoid species from the families Blissidae and Lygaeidae (sensu stricto; including the subfamilies Lygaeinae and Orsillinae) were analyzed. Fluorescence in situ hybridization (FISH) revealed that all the bugs studied possess paired bacteriomes that are differently shaped in the abdomen and harbor specific endosymbionts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 40 publications
4
72
0
1
Order By: Relevance
“…4). Transitions to vertically transmitted symbionts have been suggested to be driven by evolutionary pressures tied to specialization (35,66), but many heteropteran plant specialists retain environmentally acquired symbioses (6,67), suggesting a more nuanced evolutionary explanation. Comparative approaches focused on sister groups with different transmission strategies in the Heteroptera may yield useful biological correlations, although many additional phylogenetic and biological data will be required.…”
Section: Discussionmentioning
confidence: 99%
“…4). Transitions to vertically transmitted symbionts have been suggested to be driven by evolutionary pressures tied to specialization (35,66), but many heteropteran plant specialists retain environmentally acquired symbioses (6,67), suggesting a more nuanced evolutionary explanation. Comparative approaches focused on sister groups with different transmission strategies in the Heteroptera may yield useful biological correlations, although many additional phylogenetic and biological data will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Buchner, 1965;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2012Kuechler et al, , 2013Swiatoniowska et al, 2013 for further details). Both the histological studies of Buchner (1965Buchner ( , 1966Buchner ( , 1967) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2011Kuechler et al, , 2012Koga et al, 2012;Matsuura et al, 2012;Swiatoniowska et al, 2013) have revealed that the latter transmission of endosymbionts (termed transovarial transmission) may differ even in closely related groups of hemipterans. The endosymbiotic microorganisms may invade young germ cells termed cystocytes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, given our current state of knowledge, the most parsimonious explanation would involve a replacement from a likely ancestral endosymbiotic association (i.e., all other streblid bat flies known have an Arsenophonus-like association). Symbiont replacements are often hypothesized to result from competition among symbiont populations and/or selective pressure on the symbiont host in connection with ecological shifts (7,30,32). For blood-feeding insects, this is commonly understood as a trophic shift to a nutrient-poor diet (blood) and may have been a driving factor for the initial establishment of symbiosis in bat flies.…”
Section: Discussionmentioning
confidence: 99%